IMPLEMENTATION OF LAW NO. 16 OF 2019 CONCERNING MARRIAGE IN EFFORT TO PREVENT EARLY CHILD MARRIAGE IN THE OFFICE OF RELIGIOUS AFFAIRS, BALUSU DISTRICT, BARRU REGENCY - Mukmin Muhammad; Kamaruddin Hasan; Rismah (Sean Institute, 2022)
This research aims to find out: Implementation of Law No. 16 of 2019 concerning Efforts to Prevent Early Marriage at the Office of Religious Affairs, Balusu District, Barru Regency. And to find out the efforts to prevent early marriage at the Office of Religious Affairs, Balusu District, Barru Regency. Sources of data obtained by means of Observation, Interview, Documentation, and Triangulation. The research method uses qualitative descriptive.Based on the results of the study, it shows that the implementation of Law No. 16 of 2019 concerning Marriage in Efforts to Prevent Early Childhood Marriage at the Office of Religious Affairs in Balusu District has been implemented properly or in other words, has carried out counseling to the public regarding the dangers posed by marriage. early childhood, because all responsible parties such as marriage counselors and the local village government have made several efforts in terms of preventing early childhood marriage at the Balusu District Religious Affairs Office, one of the efforts that will be carried out is to prevent early childhood marriage. namely bringing in the health sector to socialize the consequences of early marriage so that the community is well aware and there will be no early marriage